The effect of the shade of Raintree (Albizia saman Jacq.) and Coyote (Platymiscium parviflorum Benth.) on the aerial net primary productivity and chemical composition of seminatural grassland in livestock farMON of Muy Muy, Nicaragua - Gamboa Morillo, Harold (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2009